Compressive Strength, Permeability and Porosity Analysis of Pervious Concrete by Variation of Aggregate and Compacting Method. Issue 1 (February 2021) - Sanjaya, Nico; Saloma,; Hanafiah,; Juliantina, Ika; Nurjannah, Siti Aisyah
Abstract: Pervious concrete is one of the innovation from conventional concrete which has interconnected void, thus enabling it to drain water. Compared to conventional concrete, pervious concrete has different physical and mechanical characteristics, but composed by the same material which is Ordinary Portland Cement (OPC), coarse aggregate, water, fine aggregate, and admixture. The use of fine aggregate in pervious concrete mixture is limited due to the fine aggregate can block the interconnected pores thus lowering the permeable ability of the pervious concrete. The objective of this research is to analyze the characteristics of the pervious concrete which is compressive strength, permeability, and porosity with variation of aggregate and compacting method. The pervious concrete mixture consists of 15%, 20%, and 25% of fine aggregate variations and standard rodding, proctor Hammer, and concrete vibrator as the compacting methods used. The amount of cement used on each mixture is 360 kg/m 3, w/c = 0.3, and admixture as much as 2.8% of the cement used. The slump, compressive strength, and porosity test is based on ASTM Standard, while the permeability test is based on ACI Standard. The maximum compressive strength test result is 13.103 N/mm 2 achieved by the mixture with 25% fine aggregates and compacted using concrete vibrator. The permeability test result ranged from 0.053 cm/s to 1.192 cm/s, and porosity ranged from 2.261% to 41.083%.